Pengaruh Kualitas Produk, Citra Merek, dan Kesadaran Merek Terhadap Keputusan Pembelian Produk Scarlett Whitening Pada TikTok Shop di Kota Batam - Sunarti Sunarti; Inda Sukati (Komunitas Dosen Indonesia, 2026)
This study investigates the effects of product quality, brand image, and brand awareness on consumers’ purchasing decisions for Scarlett Whitening products on TikTok Shop in Batam City. The research is motivated by the increasing number of negative consumer reviews related to the physical quality of the products, even though Scarlett Whitening continues to hold a substantial market share. A quantitative research approach with a survey design was applied, and primary data were collected through questionnaires distributed to 204 TikTok users in Batam City who had previously purchased Scarlett Whitening products. Respondents were selected using a purposive sampling technique, while data analysis was conducted using multiple linear regression. The results reveal that product quality, brand image, and brand awareness each exert a positive and significant influence on purchasing decisions. Furthermore, these three variables jointly explain 71.8% of the variance in consumer purchasing behavior. Overall, the findings indicate that maintaining superior product quality, fostering a strong brand image, and enhancing brand awareness are crucial determinants in strengthening consumer purchase decisions and improving sales performance on the TikTok Shop platform.